Enantioselective synthesis of non-biaryl atropisomers - Fugard, A (2019)
This thesis describes the development of novel methods to synthesise non-biaryl atropisomers enantioselectively. In Chapter 1, atropisomerism is defined and explored, with a focus on non-biaryl atropisomers and the literature stereoselective syntheses of chiral naphthamides. Chapter 2 discusses initial attempts to synthesise chiral naphthamides using phase-transfer catalysis, and the barriers to rotation of intermediate enol ethers, and benzylated and debenzylated naphthols are determined. Chapter 3 concerns investigations into the low barriers to rotation of these debenzylated naphthols. Chapter 4 builds on this work to develop an enantioselective synthesis of benzylated naphthamides via a dynamic kinetic resolution of the naphthol starting material. This reaction was tested on a wide variety of substrates to determine its scope and limitations, and the barriers to rotation of the chiral products were calculated.